2018
DOI: 10.1007/s11869-018-0628-7
|View full text |Cite
|
Sign up to set email alerts
|

The in situ pilot-scale phytoremediation of airborne VOCs and particulate matter with an active green wall

Abstract: Atmospheric pollutant phytoremediation technologies, such as potted-plants and green walls, have been thoroughly tested in lab-scale experiments for their potential to remove air pollutants. The functional value of these technologies, however, is yet to be adequately assessed in situ, in 'high value' environments, where pollutant removal will provide the greatest occupant health benefits. Air pollution in countries such as China is a significant public health issue, and efficient air pollution control technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 68 publications
0
25
1
Order By: Relevance
“…Comparatively, botanical biofilters process large volumes of air, treat a variety of air pollutants (i.e., VOCs, PM, and NO x ), and generally have a limited substrate depth (i.e., reduce the space occupied and maintain aesthetic appeal). In this regard, it is important that active green walls are considered within the context of their full functionality (i.e., VOC filtration [33,43], PM filtration [30,31], CO 2 reduction [40], enhanced humidity and temperature [36], biophilic benefits [68]) and not solely as phytoremediators of a limited number of pollutants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively, botanical biofilters process large volumes of air, treat a variety of air pollutants (i.e., VOCs, PM, and NO x ), and generally have a limited substrate depth (i.e., reduce the space occupied and maintain aesthetic appeal). In this regard, it is important that active green walls are considered within the context of their full functionality (i.e., VOC filtration [33,43], PM filtration [30,31], CO 2 reduction [40], enhanced humidity and temperature [36], biophilic benefits [68]) and not solely as phytoremediators of a limited number of pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Replicate biofilters were housed in open-ended poly vinyl chloride (PVC) pipe (88 mm internal diameter, 120 mm in length). Each PVC pipe contained a coconut husk-based growth substrate packed to a depth of 85 mm to represent a realistic active green wall substrate depth that would be sufficient to support plant growth, as has been tested in previous research [34,43]. Coconut husk is a favourable substrate for use as a growth substrate in botanical biofilters as it has not been associated with bioaerosol emissions [44], and has a demonstrated capacity to filter VOCs [33] and PM [30].…”
Section: Biofilter Design and Plant Selectionmentioning
confidence: 99%
“…However, different climate zones should be investigated (including hot and cold) to justify the applicability of indoor ABB systems along with the energy-saving potential. Two pilot-scale AGWs were tested in both residential housing and a classroom to assess the removal capacity of both total volatile organic compounds (TVOCs) and PM (Pettit et al, 2019a). Analysis of the investigated data confirmed the reduction of TVOC and PM concentrations to a level that the classroom's current HVAC system could not achieve in normal conditions.…”
Section: Active Botanical Biofiltration In Realistic Conditionsmentioning
confidence: 97%
“…This approach was defined as active botanical biofiltration (ABB) by Pettit et al (2018a) where Liewellyn and Dixon (2011) stated the system as the botanical indoor air biofilter (BIAB) (Llewellyn and Dixon, 2011;Pettit et al, 2018a). Moreover, researchers used several other nomenclatures to refer this same system such as an active living wall (ALW) or active green wall (AGW) system when they applied this technology to the existing living wall or green wall systems (here living wall and green wall both indicate the similar vertical greening system) (Irga et al, 2017a;Pettit et al, 2019a). So far, research has been carried out dealing with different aspects of ABB to reduce overall air pollutants, such as the impact of plant quantity and type; temperature and airflow; media substrates; plant nutrition and irrigation; and lighting.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the extreme variation amongst indoor environments, such as differently sized rooms, different layouts, different lighting conditions, different ventilation rates, different ambient air quality and different pollution sources, it is necessary to assess active green wall operation within a range of environments to truly understand whether these systems can make worthwhile improvements to the air quality of indoor environments. Nonetheless, the limited number of in situ studies that have been performed have indicated that active green walls can improve the air quality of at least some indoor environments [72]. In addition to indoor applications, commercial active green walls are currently being installed in outdoor environments in select urban centres around the globe and system performance in such environments and the removal of NOx and O3 remains an area of important future research [73].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%